FIELD EXPERIMENTATION ON WALL SURFACE TEMPERATURE WITH FABA BRICK IN HOT CONDITIONS - Vira Ansari; Eddy Prianto; Agung Dwiyanto (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The processing of coal waste into building materials from fly ash bottom ash has been stipulated in Regulation number 22 of 2021 as Non-Hazardous material, with a note that the management requirements must still meet the standards and technical requirements set out and listed in the environmental document approval. Previous studiesstated that one of the physical characteristics of the use of this waste (fly ash bottom ash) can be in improving the quality of construction materials and environmental quality. The research questions of this study are: Does the facing east orientation quantitatively receiving more heat of the morning sun than other orientations? Does FABA brick walls affect the indoor thermal performance? The wall surface temperature measurement is carried out by the field experimentation with extreme climatic conditions, both sunny and rainy weather in 2021. The results of this study found that the surface temperature profile of the brick wall oriented to the east in sunny rainy/cold weather is cooler 2 % compared to the temperature on the western side. The wall surface temperature profile in the morning is 25% warmer than the ambient air temperature in sunny weather and 9% cooler in rainy weather. wall material with FABA brick proves that the orientation, location and character of the microclimate are significant to the thermal value.